Volume 2: Coal, Biomass and Alternative Fuels; Combustion and Fuels 1985
DOI: 10.1115/85-igt-117
|View full text |Cite
|
Sign up to set email alerts
|

Smoke Emissions From Lean Well Mixed Gas Turbine Primary Zones

Abstract: Smoke emissions for a Jet Mix flame stabiliser at lean gas turbine combustor primary zone conditions are reported at a 600K operating temperature and 1 bar pressure for kerosene. The influence of pressure loss was studied, this influences the fuel and air mixing and the liquid drop size and hence has an influence on smoke emissions. Two flame stabiliser designs were studied with different fuel and air mixing rates. The results show that even for lean well mixed situations factors that influence local fuel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The present work used the conductivity technique to study the turbulent mixing of two interacting axial and radial jets at right angles, with a third jet simulated fuel injection through the radial jet. This is a common aerodynamic feature of many burners and has been used by Andrews et al (23)(24)(25)(26)(27) as the basis of a rapid mixing low NOx combustor design for gas turbine primary zones. For gaseous combustion, ultra low NOx emissions were demonstrated (23)(24)(25)(26)(27) indicating that rapid mixing was achieved.…”
Section: Interacting Radial and Axial Jet Mixing For Rapid Fuel And Amentioning
confidence: 99%
“…The present work used the conductivity technique to study the turbulent mixing of two interacting axial and radial jets at right angles, with a third jet simulated fuel injection through the radial jet. This is a common aerodynamic feature of many burners and has been used by Andrews et al (23)(24)(25)(26)(27) as the basis of a rapid mixing low NOx combustor design for gas turbine primary zones. For gaseous combustion, ultra low NOx emissions were demonstrated (23)(24)(25)(26)(27) indicating that rapid mixing was achieved.…”
Section: Interacting Radial and Axial Jet Mixing For Rapid Fuel And Amentioning
confidence: 99%
“…One method of achieving this is the Jet Mix design shown in Fig.!. This has been shown to have extremely low NOx emissions for gaseous fuels at simulated gas turbine primary zone conditions (Andrews et al, 1983;Al Dabagh et al, 1985;Abdul-Aziz and Andrews, 1985). Tests with liquid fuels (Andrews et al, 1983;Abdul-Aziz et al, 1987a,b) have shown that the system has low smoke characteristics and has only a small increase in the gaseous fuel NOx emissions.…”
Section: The Jet MIX Lean Primary Zone Designmentioning
confidence: 99%
“…The design concept of the Jet Mix stabiliser has been discussed previously (10,11,(16)(17)(18)(19)(20) and is shown in Fig.l. The design is aimed at rapid fuel and air mixing with some control over the richest local zones that can be produced.…”
Section: Design Principlesmentioning
confidence: 99%
“…Although these have some advantages, Ahmad et al (5)(6)(7)(8)(9) have shown that the NOx emissions and combustion efficiency of weak mixtures is not as good as in the present jet shear layer designs. The authors have extensively investigated various designs of jet shear layer fuelled systems for low emissions wide stability combustor primary zones (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). This work has concentrated on investigating factors that influence mixing, especially the number of air and fuel injection points (13) and the influence of pressure loss (12,14,15,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation